A Compact Dual-Band CPW-Fed MIMO Antenna for Indoor Applications - Mohamed M. Morsy (International Journal of Antennas and Propagation)
A compact dual-band multiple-input-multiple-output (MIMO) antenna for LTE700, GSM1900, and UMTS applications with high isolation is presented. To enhance impedance matching and multiband operation, two inverted L-shaped monopoles are printed in the circular slot of the ground plane. The single element design is mirrored along the diameter of the circular slot of the ground plane. A strip is employed between the two radiators in order to mitigate the mutual coupling effect and enhance the impedance matching at operating bandwidths. Moreover, two slits are inserted in the ground plane in order to disturb the current distribution between radiating elements, and hence, the isolation between elements is improved. The measured 10 dB return loss bandwidth is 100 MHz (698–798 MHz) and 359 MHz (1765-2124 MHz) over the LTE700, GSM1900, and UMTS bands. The measured isolation between the two ports is less than -13 dB over the LTE700 bands while it is recorded to be less than -17 dB over the GSM1900 and UMTS bands. In addition, parametric studies of the proposed MIMO antenna are performed, and the surface current analysis is discussed to show the effect of the isolation structure. The radiation patterns are measured, and envelope correlation coefficient is calculated. The simulated results are in good agreement with measurements.